2014
DOI: 10.3340/jkns.2014.55.3.160
|View full text |Cite
|
Sign up to set email alerts
|

Large Intracranial Aneurysm after Transsphenoidal Surgery for Pituitary Macroadenoma

Abstract: Uncontrolled cerebrospinal fluid (CSF) leakage after transsphenoidal surgery (TSS) for pituitary adenoma can lead to meningitis. Intracranial mycotic pseudoaneurysm is a rare complication in central nervous system infection. Large single pseudoaneurysm is more uncommon. Most mycotic aneurysms occur due to endocarditis. The present patient had no heart problem and was infected by CSF leakage after transsphenoidal surgery. We present a case of large ruptured mycotic pseudoaneurysm as a complication of cerebral i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…There are several case reports about the development of a postoperative pseudoaneurysm of the ICA. [ 22 23 24 37 ] Detailed review of these cases revealed that these patients were not evaluated for the presence of an aneurysm prior to surgery. [ 22 23 24 37 ] Thus, it is difficult to conclude whether there was a preexisting aneurysm as opposed to a newly-formed pseudoaneurysm.…”
Section: Discussionmentioning
confidence: 99%
“…There are several case reports about the development of a postoperative pseudoaneurysm of the ICA. [ 22 23 24 37 ] Detailed review of these cases revealed that these patients were not evaluated for the presence of an aneurysm prior to surgery. [ 22 23 24 37 ] Thus, it is difficult to conclude whether there was a preexisting aneurysm as opposed to a newly-formed pseudoaneurysm.…”
Section: Discussionmentioning
confidence: 99%